A construção do projeto poético de Manoel de Barros: da militância no partido comunista ao diálogo com Bispo do Rosário - Silva, Fernanda Martins (2018)
This research aims to comprehend the esthetic project present in the work of Manoel de Barros, through the dialogical relation established by the poet and plastic artist Arthur Bispo do Rosário. Hence, the observation of how this acclaimed author for portraying the “greatness of the tiny” used mundane elements, marginalized and even the matter of madness, through a dialogue with the illogical, in his work and in which ways, the elements and esthetic proposal of Arthur Bispo do Rosário support Barros´s work, that is, what the poetic evaluative value of Bispo to Barros is. Bispo do Rosário is considered one of the greatest Brazilian plastic artists and carried out his entire work at Colonia Juliano in Rio de Janeiro, diagnosed with schizophrenia, utilized worthless matter to build his legacy. Bispo had the mission to rebuild the world after Armageddon, and as a result, he gave meaning to such matter, as Manoel de Barros monumented the rest. From this scope, we suggest a dialogue between the poetry of Bispo and Barros, considering the significance of things through the poetic language that unite them. Inside the dialogical dimension, we also suggest analyzing the image construction that disturbs the logic in the work of both. To Manoel de Barros poetic image is a way of transcending the language. Thus, he disassemble pre-established concepts allowing a new understanding of the world, and consequently of the being from a project that aims the world´s rebuilding through these images and a dialogue with the illogical, with the disconnected, with the dreamlike and the meaningfulness of ordinary things. Barros´s dialogue with plastic arts happens in a deep way, having dedicated himself to its study for a year at the modern and contemporary art school in New York – USA, after a trip that impacted all his esthetic and political project. In this context, dialogues with plastic arts, on a general basis, are constant in his work, however, the dialogues the poet establishes with Bispo do Rosário are the ones selected here, for we believe Bispo is more than a mere reference in Barros´s work, he materializes the poet´s project to write a book that made the nothing come up. Bispo is one of Barros´s facets, having in his poetry, this way, a heavier evaluative weight in this dialogue Barros has with plastic arts. From this point of view, both Barros and Bispo do Rosário seek the remeaningfulness of things through image construction.